Investigation of Mixed Data Rate and Format Transmission in WDM Networks. - Bobrovs, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2008)
Simultaneous propagation of different modulation formats in WDM systems are evaluated numerically with OptSim simulation software at a bit rate of 2.5 Gbit/s and 10 Gbit/s using 80 km fibre length. The obtained results show the flexibility of mixed WDM networks and usability in futures solutions. Ill. 7, bibl. 5 (in English; summaries in English, Russian and Lithuanian).